Pengaruh Perilaku Konsumen Terhadap Penggunaan Uang Elektronik (Dompet Digital) Sebagai alat Pembayaran pada Masa Pandemi Covid – 19 di Kota Medan - Maria Kristina Situmorang (Magister Manajemen Universitas Muhammadiyah Sumatera Utara, 2021)
This study aims to determine and analyze the influence of consumer behavior on the use of electronic money (digital wallets) as a means of payment during the Covid-19 pandemic in the city of Medan. The population in this research was 12,185 people. The sample in this study was 100 people. The data collection technique used was a questionnaire. The data analysis technique used is multiple regression analysis. The results showed that there was an effect of consumer behavior on the use of electronic money (digital wallets) as a means of payment during the Covid-19 pandemic in the city of Medan